Nilai Indeks kerusakan pohon karet (hevea brasiliensis) di hutan rakyat kelurahan ujung gunung, kecamatan menggala, kabupaten tulang bawang.: The damage index value of rubber trees (Hevea brasiliensis) in rubber community forest Tulang Bawang Regency - Selvira; Rahmat Safe'i; Slamet Budi Yuwono; Hari Kaskoyo (PERENNIAL, 2022)
Rubber (Hevea brasiliensis) is a tree species developed in community forests because it has dual benefits in the form of wood and sap. Therefore, the condition of damage to rubber trees needs to be known as a support effort to produce high sap production and the health of smallholder rubber plants. This study aimed to determine the index value of rubber tree damage in the community forest of Ujung Gunung Village, Menggala District, Tulang Bawang Regency. Data collection is done by calculating the tree damage index value through the damage location parameters (X), type of damage (Y), and the severity of tree damage (Z) using a circular plot with a radius of 17.95 cm following the annular plot in the FHM cluster plot design. The results showed that from 111 samples of observations, the index value of tree damage was in the range of 1.2 – 5.5. The damage index includes damage to the rootstock, upper and lower stems, branches, and leaves with cancer damage type, damaged leaves, and dead branches. The location of the dominant damage occurred in leaves with the type of leaf damage, shoots, or shoots damaged with damage index values ranging from 1.2 - 1.9. However, the most significant damage index value occurred in tree damage with the location of the damage on the trunk, type of cancer damage with a severity level of 57%. Thus, the location of the trunk with the type of cancer damage significantly affects the tree's damage with the highest damage index value of 5.5, which can stop the tree from producing latex until death. Control measures can be taken by cleaning the remaining latex and applying fungicides to the stems. In addition, tapping that is organized and does not exploit can prevent damage to the stems.